1991
DOI: 10.1037/0022-3514.61.4.582
|View full text |Cite
|
Sign up to set email alerts
|

Presence of human friends and pet dogs as moderators of autonomic responses to stress in women.

Abstract: Autonomic responses were measured while 45 adult women performed a standard experimental stress task in the laboratory with only the experimenter present and 2 weeks later at home in the presence of a female friend, pet dog, or neither. Results demonstrated that autonomic reactivity was moderated by the presence of a companion, the nature of whom was critical to the size and direction of the effect. Ss in the friend condition exhibited higher physiological reactivity and poorer performance than subjects in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
253
2
9

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(275 citation statements)
references
References 27 publications
11
253
2
9
Order By: Relevance
“…It is possible that the introduction of a pet dog helps prevent obsessive behaviors, particularly repetitive actions that are characteristic of many individuals with ASD (Turner 1999), by breaking the cycle through providing a stimulating point of interest (e.g., by playing a game with the dog). It is also possible that by stroking the dog the child engages in repetitive behaviors which are viewed as less problematic by their parent; as well, stroking can bring direct physiological benefits (e.g., reductions in physical stress responses; Allen et al 1991). However, we did not collect data on the types of child-dog interactions, therefore it is not possible to support these speculations.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…It is possible that the introduction of a pet dog helps prevent obsessive behaviors, particularly repetitive actions that are characteristic of many individuals with ASD (Turner 1999), by breaking the cycle through providing a stimulating point of interest (e.g., by playing a game with the dog). It is also possible that by stroking the dog the child engages in repetitive behaviors which are viewed as less problematic by their parent; as well, stroking can bring direct physiological benefits (e.g., reductions in physical stress responses; Allen et al 1991). However, we did not collect data on the types of child-dog interactions, therefore it is not possible to support these speculations.…”
Section: Discussioncontrasting
confidence: 45%
“…This may be achieved through reducing stress in the family, and the potential for pet dogs to reduce parental stress has recently been demonstrated (Wright et al 2015). A study by Allen et al (1991) showed that stress levels reduced more in the presence of a dog compared with a friend, indicting the unique processes involved in human-animal interactions as opposed to human-human family interactions. Additionally, the dog represents a common talking point, a stress release, and a shared love which helps unite the family.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, women are most likely to feel evaluated by other women similar to them -their female friends. Empirical support for this notion can be found in a study where women with a female friend present had higher reactivity than when tested alone (32), which was attributed to the friends' supporting behaviour increasing evaluation apprehension and self-consciousness in the participants. Similarly, women receiving support from a female friend who was able to monitor their performance exhibited similar magnitude reactivity to when they were tested alone; when the friend was not able to monitor their performance (low evaluation potential) SBP reactivity was attenuated (23).…”
Section: Discussionmentioning
confidence: 59%
“…These studies suggest that women feel evaluated by females, and particularly female friends, when they are in a position where they can monitor their performance. In this previous research (23,32), women were tested only with female friends, making it impossible to discern whether women would or would not feel evaluated in the presence of supportive male friends. In a study where no overall differences in reactivity emerged between supported and unsupported participants, women who rated themselves as highly supported by their female friend exhibited greater DBP reactivity, whereas the opposite pattern emerged for men (33).…”
Section: Discussionmentioning
confidence: 99%
“…Companion dogs were often found to bring about benefits such as nonevaluative support that could act as buffer for stress (Allen, Blascovich, Tomaka and Kelsey, 1991), reduction in fear of being a victim of crime (Serpell, 1990) and staving off social needs deficits due to rejections (McConnell, Brown, Shoda, Stayton and Martin, 2011) to their owners. The importance of companion animals such as dogs and cats are valued in many parts of the world and researches have been conducted in various countries.…”
mentioning
confidence: 99%